PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA YEAKIN PLASTIC INDUSTRY - Hansen, Welly; Purba, Tiurniari (LPPM Universitas Putera Batam, 2021)
The industrial world is currently experiencing very rapid progress, this is influenced by technology that is experiencing rapid development. Such industrial developments are widely used by business people in running their business. This study aims to analyze the effect of motivation and work discipline on employee performance. Data processing using SPSS version 26 with the type of quantitative research. The results of the t test (partial) that motivation has a significant and positive effect on employee performance with t count > t table with a significance value < 0.05, namely 5.357 > 1.970 and a significant value of 0.000 < 0.05, work discipline has a positive and significant effect on employee performance with t count > t table where sig < 0.05 is 9.075 > 1.970 and sig 0.000 < 0.05. This is evidenced from the results of the F test where f count > f table with a value of sig < 0.05, namely 82.509 > 2.644 and a sig value of 0.000 <0.05 which states that motivation and work discipline have a positive and significant effect simultaneously on employee performance at PT. Yeakin plastic industry Batam.